2023
DOI: 10.1021/acsami.3c03982
|View full text |Cite
|
Sign up to set email alerts
|

Contracted Fe–N5–C11 Sites in Single-Atom Catalysts Boosting Catalytic Performance for Oxygen Reduction Reaction

Abstract: Promoting the catalyst performance for oxygen reduction reaction (ORR) in energy conversion devices through controlled manipulation of the structure of catalytic active sites has been a major challenge. In this work, we prepared Fe−N−C single-atom catalysts (SACs) with Fe−N 5 active sites and found that the catalytic activity of the catalyst with shrinkable Fe−N 5 −C 11 sites for ORR was significantly improved compared with the catalyst bearing normal Fe−N 5 −C 12 sites. The catalyst C@PVI-(TPC)Fe-800, prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…3a–d). 97 Li and co-workers also proved that the Fe–N 5 active sites with the asymmetric electron depletion zone over the metal center can improve the activation of intermediates and decreased the energy barrier of the rate-determining step (Fig. 3e–g), which thus accelerated the intrinsic ORR and OER processes, leading to a superb battery performance.…”
Section: Engineering Nbm Sacsmentioning
confidence: 92%
“…3a–d). 97 Li and co-workers also proved that the Fe–N 5 active sites with the asymmetric electron depletion zone over the metal center can improve the activation of intermediates and decreased the energy barrier of the rate-determining step (Fig. 3e–g), which thus accelerated the intrinsic ORR and OER processes, leading to a superb battery performance.…”
Section: Engineering Nbm Sacsmentioning
confidence: 92%
“…Local coordination manipulation, which involves altering the type and number of ligand atoms, modulates the electronic structure of the metal center, including electron density and d-orbital occupancy. 63–70 Such regulation can influence the adsorption capacity of the metal center for reactants and the activation energy, creating active sites with specific geometric configurations that may be more favorable for the transition states of particular reactions, thereby reducing the reaction energy barrier and improving reaction kinetics and catalytic activity. Zhang et al demonstrated that modulating the spatial distance between phosphorus doping atoms and single-atom iron sites can enhance ORR activity, thereby revealing the inductive effect between single-atom sites.…”
Section: Improvement Strategies For Activitymentioning
confidence: 99%
“…Layered double hydroxides (LDHs), known as a benchmark for OER activity, have attracted great focus for water splitting and metal-air batteries. Nevertheless, during the synthesis procedure, agglomeration and lower conductivity plague pristine LDHs and, hence, their electrochemical active surface area (ECSA) will decrease. , Meanwhile, the lack of ORR catalysis indicates that a single LDH fails to satisfy the requirement of a catalyst for RZABs. Therefore, constructing hierarchical structures that combine LDHs with conductive ORR active material is considered an effective solution .…”
Section: Introductionmentioning
confidence: 99%